2008
DOI: 10.1117/1.2952298
|View full text |Cite
|
Sign up to set email alerts
|

Effect of liposomal confinement on photothermal and photo-oximetric fluorescence lifetimes of photosensitizers with varying hydrophilicity

Abstract: The time-resolved fluorescence of photosensitizers (PSs) of varying hydrophobicities, di-and tetrasulfonated Al phthalocyanines (Al-2 and Al-4), and Photochlor (HPPH), was investigated in liposomes used as cell-mimetic models. Using frequency-and time-domain apparatus, the fluorescence lifetime, tau(fluo), was compared for PSs free in aqueous solution and in a liposome-associated state at varied temperatures (25 to 78 degrees C) and oxygen concentrations (0-190 microM). The analysis of tau(fluo) revealed diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…TRF studies relevant to different PDT photosensitizers have been reported by several research groups in the past decades [31,43,45,[70][71][72][73][74][75][76]. FDA-approved PDT photosensitizers include Photofrin ® , 5-aminolevulinic acid-induced protoporphyrin IX (ALA-PpIX), and verteporphyrin, Other photosensitizing agents in research stage, such as mTHPC (m-tetrahydroxyphenylchlorin, Foscan ® ), phthalocyanine (Pc) compounds, and chlorin-based compounds (i.e., HPPH), also showed promising results in terms of their singlet oxygen yield and more red-shifted absorption bands [77].…”
Section: Time-resolved Studies Of Pdt Photosensitizers In Solution Anmentioning
confidence: 99%
See 1 more Smart Citation
“…TRF studies relevant to different PDT photosensitizers have been reported by several research groups in the past decades [31,43,45,[70][71][72][73][74][75][76]. FDA-approved PDT photosensitizers include Photofrin ® , 5-aminolevulinic acid-induced protoporphyrin IX (ALA-PpIX), and verteporphyrin, Other photosensitizing agents in research stage, such as mTHPC (m-tetrahydroxyphenylchlorin, Foscan ® ), phthalocyanine (Pc) compounds, and chlorin-based compounds (i.e., HPPH), also showed promising results in terms of their singlet oxygen yield and more red-shifted absorption bands [77].…”
Section: Time-resolved Studies Of Pdt Photosensitizers In Solution Anmentioning
confidence: 99%
“…How these factors affect lifetime measurements of the photosensitizers will be further discussed. [43] 10 ns (Organic solution) [70] 5.5 ns (Mitochondria, MLL) [70] 13.3 ns (Monomer, mitochondria) [70] 13.6 ns (Monomer, mitochondria) [45] 8.5 ns (Aggregates, mitochondria) [45] 8.0 ns (Aggregates, mitochondria) [78] 4.8 ns (Cell membrane) [78] 1.0 ns (Aggregates, mouse model) [31] 13 ns (Monomers, mouse model) [31] 5 µg/mL 0.06-6 µg/mL 7.6 ns (liposome confined) [74] 6.4 ns (tissue phantom) [75] 4.3 ns (mouse tumor, before PDT) [75] 5.0 ns (mouse tumor, after PDT) [75] …”
Section: Time-resolved Studies Of Pdt Photosensitizers In Solution Anmentioning
confidence: 99%
“…However, once encapsulated in liposomes, both the Zn-and Cu-metalated PSs exhibited enhanced emission in the red. The increased emission and extension in PS lifetime due to the incorporation of PS in liposomes have been explained elsewhere (Noiseux et al 2008, Mermut et al 2008. Briefly, the insertion of the PS into a more favorable microenvironment (i.e.…”
Section: Emission Characteristics Of Ps In Solu and In Cellular Phantomsmentioning
confidence: 99%
“…Details of the luminescence lifetime instrument and measurements, based on a time-correlated single photon counting system (TCSPC), have been described elsewhere (Mermut et al 2008). Briefly, excitation of the Soret band of the PS in solvent or confined in liposomes was achieved using a 400 nm, picosecond laser diode (PDL 800-B driver and LDH-P-C-405 diode, Picoquant GmbH, Germany), with an average output of 900 μW and a pulse duration of ∼150 ps at a repetition rate of 40 or 20 MHz.…”
Section: Magnet-coupled Luminescence Lifetime Apparatusmentioning
confidence: 99%
“…Hydrogels are polymeric materials with hydrophilic structures capable of holding large amounts of water in their three-dimensional mesh structures with physical properties similar to those of living tissues (196,197). These are widely used for the controlled release of hydrophilic drugs including water soluble PCs and MPCs (198)(199)(200). They can combine chemo-photodynamic therapy (201) or can be used for in vivo imaging (202).…”
Section: Formulations and Dds Of Pcs And Mpcsmentioning
confidence: 99%